Glioependymal Cyst of Frontal Lobe. Issue 2 (May 2015) - Qi, Xuchen; Xie, Dajiang; Wan, Yingfeng; Zhu, Yinxin; Ma, Zhiming; Chen, Keng; Wang, Yirong; Yang, Shuxu
<x xml:space="preserve">Abstract</x> Glioependymal cysts are rare in the central nerve system, and they may arise from the lining ependymal cells. We herein present a case of a giant glioependymal cyst and discuss the clinical presentation, pathogenesis, and treatment options for this lesion. A 38-year-old man was admitted to our hospital on an emergency basis because of a sudden onset of whole-body spasm for minutes and unconsciousness for hours. Electroencephalography examination indicated mild abnormality. Magnetic resonance imaging demonstrated a well-defined homogeneous parenchymal cystic mass located in his right frontal lobe. The resection of the most of cystic wall and epileptogenic focus were introduced. Pathologic examination revealed that it was a glioependymal cyst. The postoperative course was uneventful, no infection and cerebrospinal fluid leak happened.